2023
DOI: 10.1097/ms9.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

Computer-related ophthalmic syndrome in teachers of a University of the Province of Cañete

Abstract: Introduction and Importance: Virtual education has impacted the vision of people during the coronavirus pandemic, as by spending more time on the computer, it compromises the eye health of the person causing long-term visual problems. So the objective of this investigation is to assess computer-related ophthalmic syndrome in teachers of a University of the Province of Cañete. Methods: This is a quantitative, nonexperimental, descriptive, cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is also important to mention that mindfulness programmes and meditation can be effective in reducing stress and improving the emotional well-being of employees with burnout symptoms 51 , 52 . These programmes focus on teaching mindfulness and meditation techniques to help people manage their stress response and improve their ability to concentrate and make decisions 53 - 55 . It is important to note that while the above treatments are effective in reducing the effects of burnout, it is necessary for the healthcare facility to take a holistic approach that addresses the underlying causes of work-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to mention that mindfulness programmes and meditation can be effective in reducing stress and improving the emotional well-being of employees with burnout symptoms 51 , 52 . These programmes focus on teaching mindfulness and meditation techniques to help people manage their stress response and improve their ability to concentrate and make decisions 53 - 55 . It is important to note that while the above treatments are effective in reducing the effects of burnout, it is necessary for the healthcare facility to take a holistic approach that addresses the underlying causes of work-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…In Peru, evaluated the levels and intensity of visual computer syndrome and found that the prevalence was mild (9.2%). In the same way, another investigation was also carried out in Peru in the postpandemic period and found that the intensity of computer visual syndrome in teachers was mild (1.6%) (Uribe-Hernández et al, 2023).…”
mentioning
confidence: 91%